Algorytmy analizy niezawodności systemów - Kulik, Czesław (Wydział Prawa i Administracji UAM, 1975)
The infallibility of system may be defined as the probability of task fulfilment. One has to distinguish the beginning infallibility and the infallibility function which expresses the influence of time upon the infallibility of system. In practice the function is unknown and therefore it has to be estimated on the basis of sampling. The author shows us how to estimate the function with help of computer model.
Analysis Algorithms of Systems